People's Palm Oil Replanting (PSR) Fund Assistance Scheme at Jaya Usaha Sempurna Producer Cooperative in Mega Timur Village, Sui Ambawang District, Kubu Raya Regency, West Kalimantan - Rudi Hartono (Pascasarjana, Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
This research discusses the implementation of the People's Palm Oil Replanting (PSR) program implemented by the Indonesian government as an effort to increase the productivity and welfare of oil palm farmers, especially in areas with unproductive oil palm plantations. This program provides financial assistance of IDR 30 million per hectare which is used to replace old oil palm plants with superior seeds that are more productive. This research method uses a qualitative method with a descriptive research type. Primary sources focused on the Jaya Usaha Sempurna Producer Cooperative located in Mega Timur Village, Sui Ambawang District, Kubu Raya Regency, West Kalimantan, which is one of the legal farmer groups that received the assistance. This study aims to evaluate the PSR grant scheme received by the cooperative, analyze its impact on oil palm productivity, and identify challenges faced in implementing the program. The methodology used in this research is a descriptive qualitative approach, with data collection through in-depth interviews, field observations, and document studies related to the PSR program. This study concludes that although the PSR program has shown positive results, improvements are still needed in the aspects of administration, extension, and coordination between related parties to optimize the benefits of the program for smallholder oil palm farmers